(untitled) (Daffodil International University Journal of Science and Technology, 2010)
A study was performed on the jute-cotton union fabric to show the effect of sizing on the properties of union fabric. Here, the cotton yarn was used in the warp direction and jute yarn was used in the weft direction. The size material was used only for warp yarn that is for cotton yarn. From the experimental results, it was seen that the strength of the sized union fabric was better than the unsized union fabric although the other properties were similar to each other. Comparing the properties of union fabric with 100% cotton fabric, union fabric (jute-cotton) may be the replacement of 100% same category of cotton fabric. Key words: Jute, union fabric, cotton fabric, warp yarn, weft yarn, sized, properties. DOI: 10.3329/diujst.v4i2.4363 Daffodil International University Journal of Science and Technology Vol.4(2) 2009 pp.36-38